El razonamiento lógico-matemático en el proceso de enseñanza-aprendizaje en los estudiantes de educación básica media de la Unidad Educativa “Cotaló” en el periodo, octubre 2016 – agosto 2017 - Tubón Escobar, Fernando Javier (2017)
The present research work has as its purpose the research carried out for the research on Mathematical Reasoning-Logic in the process of Teaching-Learning to consolidate logical reasoning mathematical, in order to achieve this purpose raised to seek a diagnostic vision of What is the situation of students of General Basic Education Media, about which methodological strategies are used and changes are established in the educational management of the area of mathematics, in order to ensure academic quality. In addition, to have sufficient information about reasoning, how to improve it and develop it so that we can move forward to establish competitive programs linked to the production of scientific and human knowledge….